Do you get what i'm not saying?: On dance as a Subversive declaration of love - Lilja, Efva (Sweden Ellerströms, 2012)
All my life I have observed and studied how and why people move. As a choreographer I use my observations and try out different expressions. Through dance, text and imagery I invite all of us into a loveful concept where everything is possible. I write about art and survival strategies. I write to provide fresh power in lifes uphill challenges and to drive out the treacherous feeling of loneliness that kicks in when you face your own shortcomings. I write about the search for meaning in a philosophical sense with my own attitude to choreography, artistry and love as a starting point. A poesy of dance.